2016
DOI: 10.1002/wnan.1407
|View full text |Cite
|
Sign up to set email alerts
|

Using nanobiotechnology to increase the prevalence of epigenotyping assays in precision medicine

Abstract: Epigenetic silencing of genes that are important for DNA repair, cell cycle control, apoptosis, and cellular interactions with the extracellular matrix has been causally linked to several subtypes of cancer. Translating this knowledge of the implications of promoter methylation to wide and routine use in clinical pathology laboratories has been more challenging than the case of genetic analyses because epigenetic modifications do not change the underlying sequence of the affected nucleic acid, rendering polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The titration curve in the presence of genomic DNA looks very similar to that without genomic DNA, and the limit of detection in the presence of genomic DNA was determined to be 5 pM target DNA based on a two‐sample Wilcoxon test at a significance level of 0.01. However, further improvement in sensitivity is still required in order for the assay to be useful for clinical samples, where only 10 6 copies of the genome may be available and sub‐pM sensitivity is required . Such improvements could potentially be made by either using a system with improved transport properties to concentrate the target DNA on a smaller number of beads, thus increasing the amount of target captured and MBD bound per bead, or by using more sensitive detection mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The titration curve in the presence of genomic DNA looks very similar to that without genomic DNA, and the limit of detection in the presence of genomic DNA was determined to be 5 pM target DNA based on a two‐sample Wilcoxon test at a significance level of 0.01. However, further improvement in sensitivity is still required in order for the assay to be useful for clinical samples, where only 10 6 copies of the genome may be available and sub‐pM sensitivity is required . Such improvements could potentially be made by either using a system with improved transport properties to concentrate the target DNA on a smaller number of beads, thus increasing the amount of target captured and MBD bound per bead, or by using more sensitive detection mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, all clinical methylation testing uses bisulfite conversion of DNA followed by PCR or sequencing . In bisulfite conversion, unmethylated cytosines are chemically converted to uracil while methylated cytosines remain unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2–4 The utility of promoter methylation as a biomarker for cancer diagnostics is demonstrated by the commercially available tests Cologuard ® and Epi ProColon ® for colorectal cancer screening. 57 While there are only a few gene promoters that are routinely evaluated for methylation at this time, 8,9 studies have shown tumor-associated promoter methylation of more than 45 genes in various types of cancers. 10 …”
Section: Introductionmentioning
confidence: 99%
“…9,11 Such methods have numerous drawbacks. For example, large quantities of DNA are required because 90% can be degraded during the conversion step, and without careful optimization and control of the reaction conditions, false positives and negatives are common.…”
Section: Introductionmentioning
confidence: 99%